The Influence of Service Quality and Room Rates on Guest Loyalty at UNP Hotel & Convention Center - Yunisha Eureka; Yorike Dwi Putri; Aditya Warman; Feri Ferdian (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Purpose: This study aims to elucidate the profound influence of service quality and room rates on hotel guest loyalty within the context of UNP Hotel & Convention Center. Method: Employing an explanatory research design with a quantitative approach, this study examines the interplay between service quality, room rates, and hotel guest loyalty. The study focuses on a population of repeat guests at UNP Hotel & Convention Center. Data was collected from 50 respondents through purposive sampling using a meticulously designed questionnaire. The collected data was subjected to descriptive analysis and path analysis, with the proposed model evaluated using the Smart Partial Least Squares Structural (PLSS) assessment. Results: The findings underscore a compelling and statistically significant correlation between service quality, room rates, and guest loyalty. This highlights a crucial implication for the hotel industry to prioritize and meticulously manage service quality and room pricing in order to foster and amplify guest loyalty. Contribution: This research underscores the pivotal role of service quality and room rates in nurturing guest loyalty at UNP Hotel & Convention Center. The study reaffirms that guest loyalty is intricately tied to the anticipated service quality and pricing. As such, maintaining service quality at par and ensuring competitive room rates could potentially lead to higher guest retention and choice of the hotel. Conversely, a decline in either service quality or competitive pricing may precipitate diminished guest loyalty